Cryogenic anion photoelectron spectroscopy apparatus with filament ionizer using velocity map imaging - An, Sejun (2020)
The new design of the spectroscopy apparatus for cryogenic anion photoelectron spectroscopy consists of velocity map imaging (VMI) and filament ionization source as described in Figure.1. Quadrupole mass filter delivers mass-selected ions into a copper quadrupole ion trap (QIT) that is cryogenically cooled by a closed-cycle cryostat. Especially, copper QIT has a better ability to decrease the temperature of ions trapped compared to normal QIT made from stainless steel.[3] The improved cooling efficiency of copper QIT makes ions not to excite to vibrational state, so it enables us to observe vibration-controlled reaction dynamics. A cryogenically cooled ion packet is extracted from QIT and travels in the Wiley-McLaren time of flight (TOF) region. Both deflectors and einzel lenses fix the turned beam before entering the VMI region. Also, SIMION simulation provides proper electrostatic ion optics and predicts the ion pathway. Based on the simulation, we optimized this described design for increasing the number of focused ions in the interaction region. By using the above system, we obtained a mass spectrum confirming that the TOF system operates well to perform a further experiment.